2014
DOI: 10.1161/strokeaha.114.005245
|View full text |Cite
|
Sign up to set email alerts
|

Different Doses of Recombinant Tissue-Type Plasminogen Activator for Acute Stroke in Chinese Patients

Abstract: In America and Europe, the current recommended dose of recombinant tissue-type plasminogen activator (r-tPA) for acute ischemic stroke is 0.9 mg/kg, but a similar study with this dosage has never been replicated in a controlled trial in East Asia. A lower dose (0.6 mg/kg) of r-tPA was used in Japan and was proved to have similar outcomes compared with a dose of 0.9 mg/kg in Western countries.1,2 However, the Safe Implementation of Thrombolysis in Stroke-Non-European Union World (SITS-NEW) study demonstrated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
70
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(75 citation statements)
references
References 27 publications
(15 reference statements)
5
70
0
Order By: Relevance
“…Patients who provided blood samples for D-dimer level measurement after the initiation of rt-PA within 24 h after stroke onset were included. In our hospital, the therapeutic window of rt-PA was up to 4.5 h and the dose of rt-PA varied from 0.6 to 0.9 mg/kg depending on age [10] .…”
Section: Study Subjectsmentioning
confidence: 99%
“…Patients who provided blood samples for D-dimer level measurement after the initiation of rt-PA within 24 h after stroke onset were included. In our hospital, the therapeutic window of rt-PA was up to 4.5 h and the dose of rt-PA varied from 0.6 to 0.9 mg/kg depending on age [10] .…”
Section: Study Subjectsmentioning
confidence: 99%
“…46,47 Additionally, the Taiwan Thrombolytic Therapy for Acute Ischemic Stroke (TTT-AIS) Study Group found the dose of 0.9 mg/kg of r-tPA to be suboptimal in Chinese patients with higher rates of SICH and found that in patients aged 71 to 80, a lower dose of 0.6 mg/kg was associated with better outcome. 44 These findings have not been confirmed through randomized controlled trials. The practice of administering lower doses of r-tPA for select high-risk patients is not followed in the United States.…”
Section: Risk Factors For Sich and Pathophysiologymentioning
confidence: 92%
“…1 There are some who propose the use of lower doses of r-tPA in populations at higher risk of ICH, such as East Asian populations, as a way to decrease the risk of bleeding. 43,44 For example in Japan, 0.6 mg/kg of r-tPA is the only approved dose since 2005 for acute stroke presenting within 3 hours of symptom onset, based on the results of the Japan Alteplase Clinical Trial (J-ACT) 45 and supported by J-ACT2 and the Japan post-Marketing Alteplase Registration Study (JMARS). 46,47 Additionally, the Taiwan Thrombolytic Therapy for Acute Ischemic Stroke (TTT-AIS) Study Group found the dose of 0.9 mg/kg of r-tPA to be suboptimal in Chinese patients with higher rates of SICH and found that in patients aged 71 to 80, a lower dose of 0.6 mg/kg was associated with better outcome.…”
Section: Risk Factors For Sich and Pathophysiologymentioning
confidence: 99%
“…However, studies to determine the optimal dose of alteplase for Asian patients have produced conflicting findings. A study in Taiwan that included 1,004 patients who were treated with 0.6-0.9 mg/kg alteplase concluded that a lower dose was associated with a better outcome in patients aged 71-80 years 6 . Similarly, a multicentre registry study in South Korea that included 1,526 patients concluded that the effects of 0.6 mg/kg alteplase were comparable to those of 0.9 mg/ kg 7 .…”
mentioning
confidence: 99%